A socio-cultural study of learning and teaching science in early learning centres - Blake, Elaine J. (Curtin University, 2013)
This study investigated, from a socio-cultural perspective, the science learning experiences of 3- and 4- year old children in Early Learning Centres (ELCs). Specifically, it has produced the SCALTELC-S theoretical framework which has potential to inform both research and practice for Early Childhood Education (ECE); seven case studies to provide grass roots evidence for practitioners; and a cross-case analysis. The findings reveal implications for ECE practitioners; for undergraduate training; for professional learning; and for future research and theorising.